Virtual water requirement of cow milk production under two different dietary strategies - RIASI, MITRA; EBRAHIMI, SEYED HADI; JAVADMANESH, ALI (The Indian Journal of Animal Sciences, 2021)
Nutritionists have liberty to choose various feeds for formulating a balanced ration depending upon the nutritive value, availability and feed cost. Although final target in an alternative ration is to obtain similar energy, protein and other nutrients, it would be favourable to consider virtual water (VW) requirement which must be spent while making a balanced ration. This paper compared two isonitrogenous and isocaloric balanced dairy cow rations for their VW requirements. VW in the maize silage-based ration was greater than that of alfalfa and wheat straw-based diet (39.73 versus 34.45 m3). It was also found that by-product feeds such as molasses, beet sugar pulp, corn gluten, and soybean meal require a lesser amount of VW, thus, they could be the best candidates to be used as much as conventional main feeds in the ration of dairy cattle for decreasing VW requirement of milk. Using feeds with less water utilization could reduce water requirement for milk production up to 12%.